Clinical application of amplitude processing of echocardiographic images. Issue 6 (June 1981) - Logan-Sinclair, R; Wong, C M; Gibson, D G
Abstract : In order to assess the possible clinical value of measuring regional amplitude of ultrasound reflected from intracardiac structures, two-dimensional echocardiographic images from 20 normal subjects and 70 patients with heart disease were processed by modulation of both colour and intensity to represent grey scale. Maximum echo intensity was consistently recorded from the pericardial interface behind the posterior left ventricular wall, and this was taken as 100 per cent. In the normal heart, central fibrous body reflected at 64 +/- 5 per cent, and mitral and aortic valves at 35 +/- 5 per cent and 36 +/- 8 per cent, respectively. Normal septal myocardium gave a valve of 33 +/- 8 per cent and posterior wall of 23 +/- 6 per cent. Consistent increases were recorded from prosthetic mitral valves in 20 patients, and also from the anterior cusp of the mitral valve (54 +/- 11%) in 20 patients with rheumatic heart diseases. In all of 15 patients with left ventricular involvement caused by coronary artery disease, septal echo amplitude was increased in all to 71 +/- 11 per cent, and localised increases were also noted in the posterior wall, subendocardially, or in one or both papillary muscles. Similar focal changes were noted in five, and increases in septal density in 10 of 15 patients with left ventricular hypertrophy and in 12 of those with mitral valve disease. Thus, measurement of regional echo amplitude is possible without degradation of the quality from standard two-dimensional cardiac images. Abnormalities are particularly common in left ventricular disease where their distribution corresponds to that described for fibrous tissue.